This action might not be possible to undo. Are you sure you want to continue?
length 4
1 Some notations
In this paper, C will denote various large absolute constants, and c will
denote various small absolute constants.
[a, b] denotes the integers from a to b inclusive. Similarly deﬁne the
[a, b), etc. If E is a set, [E[ will denote the cardinality of E. N will be
00
a large integer, and 0 < δ < 1 will be a parameter, and ε = ε(δ) > 0 be
a quantity depending continuously on δ.
Let M = M(N) be a slowly growing function of N such that ε
−C
<
M < N
c
; one could take for instance M = log(N), although one can
get away with a much larger M actually. The exact choice of M is only
important if one is interested in the dependence of N on δ to be chosen
later.
For any function f on Z
N
, deﬁne the Fourier transform
ˆ
f by
ˆ
f :=
m∈Z
N
f(m) exp(2πimn/N),
and deﬁne the Wiener norm f
A
∞ by
f
A
∞ := 
ˆ
f
l
∞
(Z
N
)
= sup
n∈Z
N
[
ˆ
f(n)[,
we also deﬁne the modiﬁed A
∞
norm f
˙
A
∞
by
f
˙
A
∞
:= 
ˆ
f
l
∞
(Z
N
−{0})
.
We write Y X if Y is not of the form o(X).
01
2 The main idea of the proof
Szemer´edi asserts that for any integers k, if N is suﬃciently large de
pending on δ and k, then every set E ⊂ [0, N] with [E[ δN must
contain a nontrivial arithmetic progression of length k.
We are going to deal with the case k = 4.
The main idea is to show by induction. Let S be the set of all
0 < δ < 1 such that the Szemer´edi theorem hold for k = 4. It is
easy to see that all the δ > 3/4 belong to S, since there is at least one
of a, a + 1, a + 2, a + 3 lies in A, furthermore, we shall prove that if
δ +ε(δ) ∈ S then δ ∈ S.
Assume these, we can give the proof of the theorem.
Proof. Consider the inﬁmum δ
0
of S, now claim δ
0
= 0. If not, δ
0
> 0,
and since δ
0
+ε(δ
0
) ∈ S, we get δ
0
∈ S by induction. By the continuity
of ε, we get
δ +ε(δ) → δ
0
+ε(δ
0
), δ → δ
0
−.
02
Therefore there exists δ
1
< δ
0
such that
δ
1
+ε(δ
1
) = δ
0
,
we get δ
1
∈ S by induction, contradict to the inﬁmum of δ
0
.The proof is
done.
Fix δ, let N be a prime suﬃciently large depending on δ and ε, and
let E ⊂ [0, N) be such that [E[ δN, by reﬁning E if necessary we may
assume that
[E[ = δN (1)
we can assume that
[E ∩ P[ (δ +ε)[P[ (2)
for all arithmetic progressions P ⊂ [0, N) of length M by induction.
This is the only place where we shall use the induction hypothesis.
03
3 Proof of the induction above
Lemma 3.1. We have
[E ∩ P[ δ[P[ +O(ε[P[) (3)
for all Z
N
arithmetic progression P of length [P[ M
3
Proof. Let r = 0 be the spacing of an arithmetic progression P in Z/NZ.
(i) if 0 < [r[ < N/M. Then we can partition P into the disjoint union of
genuine arithmetic progressions of the same step size r, simply by making
a cut every time the progression wraps around the end of 1, , N.
Except possibly for the ﬁrst and last progression, each of the genuine
progressions has length at least M, and so the density of A in those
genuine progressions is at most δ +ε by (2). Adding up all these density
estimates for those genuine progressions of length at least M, we obtain
the bound
[E ∩ P[ (δ +ε)[P[ + 2M.
04
(ii) Assume r is arbitrary. Consider the ﬁrst O(M) multiples of r in Z/NZ.
By the pigeonhole principle, two of them must be < N/M apart, thus
we can ﬁnd a nonzero j = O(M) such that [jr mod N[ < N/M. We
can then partition P into [j[ disjoint progressions, all of length ∼ [P[/[j[,
with step size jr mod N. Applying the previous estimate to all of these
progressions and adding up, we obtain
[E ∩ P[ (δ +ε)[P[ + 2[j[M (δ +ε)[P[ +O(M
2
),
and the claim follows if [P[ is large enough.
We can show that (1) and (3) will imply
1
E

˙
A
∞
= O(εN), (4)
and
k∈Z
N
1
E∩(E+k)

˙
A
∞
= O(εN
2
). (5)
05
Assume (4) and (5) hold, we show that E contains ∼ δ
4
N
2
+ O(ε
1
4
N
2
)
genuine arithmetic progression of length 4, and the induction follows.
It suﬃces to show that
a,r∈Z
N
1
E
(a)1
E
(a +r)1
E
(a + 2r)1
E
(a + 3r) ∼ δ
4
N
2
+O(ε
1
4
N
2
) (6)
where E
= E ∩ [0.4N, 0.6N], since the r = 0 contribution is negligible
if N is suﬃciently large. From (1) and (3), we see that
[E`E
[ = [E ∩ (0.6N, 1.4N)[ (δ +ε)0.8N
hence we have
[E
[ = δ
N
for some δ
∼ δ. Write
f(a) =
r∈Z
N
1
E
(a +r)1
E
(a + 2r)1
E
(a + 3r).
It suﬃces to show that
a∈E
(f(a) −δ
δ
2
N) = O(ε
1
4
N
2
).
06
By CauchySchwarz, it suﬃces to show that
a∈E
(f(a) −δ
δ
2
N)
2
= O(ε
1
2
N
3
).
We need to show that
a∈Z
N
(f(a) −δ
δ
2
N)
2
= O(ε
1
2
N
3
).
Lemma 3.2. For any a, b, c ∈ Z
N
−¦0¦ we have
k,l,m∈Z
N
:ak+bl+cm=0
f
1
(k)f
2
(l)f
3
(m) f
1

2
f
2

2
f
3

A
∞ (7)
Similarly for permutations.
Proof. We can rewrite the left hand side of (7) as
1
N
n∈Z
N
ˆ
f
1
(an)
ˆ
f
2
(bn)
ˆ
f
3
(cn),
07
which can then be estimated using CauchySchwarz by
1
N

ˆ
f
1

2

ˆ
f
2

2
f
3

A
∞.
The claim then follows from Plancherel’s theorem.
Corollary 3.3. For any a, b, c ∈ Z
N
`¦0¦, we have
k,l,m∈Z
N
:ak+bl+cm=0
f
1
(k)f
2
(l)f
3
(m) = N
2
E(f
1
)E(f
2
)E(f
3
)+O(f
1

2
f
2

2
f
3

˙
A
∞
).
(8)
Similarly for permutations.
Proof. Note that
f
˙
A
∞
= f −E(f)
A
∞. (9)
Then the corollary can be got from Lemma 3.2, (9)and the identity
k,l,m∈Z
N
:ak+bl+cm=0
(f
1
(k) −E(f
1
))(f
2
(l) −E(f
2
))(f
3
(m) −E(f
3
))
=
k,l,m∈Z
N
:ak+bl+cm=0
f
1
(k)f
2
(l)f
3
(m) −N
2
E(f
1
)E(f
2
)E(f
3
)
08
.
Proposition 3.4. For any F ⊂ Z
N
, we have
u∈Z
N
[[F ∩ (E +u)[ −δ[F[[ = O(εN
2
). (10)
Proof. It suﬃces to show
u∈A
([F ∩ (E +u)[ −δ[F[) = O(εN
2
)
for arbitrary A, F ⊂ Z
N
. From (4) and Lemma 3.2, we see:
[
u∈A
([F ∩ (E +u)[ −δ[F[)[ = [
u,k∈Z
N
1
A
(u)1
F
(k)(1
E
(k −u) −δ)[
1
A

2
1
F

2
1
E
−δ
A
∞
N1
E

˙
A
∞
= O(εN
2
),
and the claim follows.
09
Remark: In Lemma 3.4, if we take F = E, we get
u∈Z
N
[[E ∩ (E +u)[ −δ
2
N[ = O(εN
2
).
Hence we get for all but at most O(ε
1
2
N) values of u such that
[E ∩ (E +u)[ = δ
2
N +O(ε
1
2
N). (11)
By Lemma 3.4, take F = 2E = ¦2e : e ∈ E¦, we get
010
a∈Z
N
(f(a) −δ
δ
2
N) =
a∈Z
N
(
r∈Z
N
1
E
(a +r)1
E
(a + 2r)1
E
(a + 3r) −δ
δ
2
N)
=
b∈Z
N
(
r∈Z
N
1
E
(b)1
E
(b +r)1
E
(b + 2r) −δ
δ
2
N)
=
b∈Z
N
r∈Z
N
1
E
(b)1
E
(b +r)1
E
(b + 2r) −δ
δ
2
N
2
=
b∈E
(
r∈Z
N
1
E
(b +r)1
E
(b + 2r) −δ
2
N)
=
b∈E
(
u∈Z
N
1
E
(u)1
E
(2u −b) −δ
2
N)
=
b∈E
([2E ∩ (E +b)[ −δ
2
N)
= O(εN
2
).
011
Hence we have
a∈Z
N
f(a) = δ
δ
2
N
2
+O(εN
2
).
Therefore
a∈Z
N
(f(a) −δ
δ
2
N)
2
= O(ε
1
2
N
3
)
⇐⇒
a∈Z
N
f
2
(a) −2δ
δ
2
N
a∈Z
N
f(a) +δ
2
δ
4
N
3
= O(ε
1
2
N
3
)
⇐⇒
a∈Z
N
f
2
(a) = δ
2
δ
4
N
3
+O(ε
1
2
N
3
)
012
By Corollary 3.3 and (5),
a∈Z
N
f
2
(a)
=
a∈Z
N
r∈Z
N
s∈Z
N
1
E
(a +r)1
E
(a +s)1
E
(a + 2r)1
E
(a + 2s)1
E
(a + 3r)1
E
(a + 3s)
=
a∈Z
N
u∈Z
N
r∈Z
N
1
E
∩(E
+u)
(a +r)1
E∩(E+2u)
(a + 2r)1
E∩(E+3u)
(a + 3r)
=
u∈Z
N
b,r∈Z
N
1
E
∩(E
+u)
(b)1
E∩(E+2u)
(b +r)1
E∩(E+3u)
(b + 2r)
=
u∈Z
N
N
−1
[E
∩ (E
+u)[[E ∩ (E + 2u)[[E ∩ (E + 3u)[ +O(N
u∈Z
N
1
E∩(E+3u)

˙
A
∞
)
=N
−1
u∈Z
N
[E
∩ (E
+u)[[E ∩ (E + 2u)[[E ∩ (E + 3u)[ +O(εN
3
)
Hence it suﬃces to show
u∈Z
N
[E
∩ (E
+u)[[E ∩ (E + 2u)[[E ∩ (E + 3u)[ = δ
2
δ
4
N
4
+O(ε
1
2
N
4
)
013
By the remark after the lemma 3.4,
[E ∩ (E + 2u)[ = δ
2
N +O(ε
1
2
N),
[E ∩ (E + 3u)[ = δ
2
N +O(ε
1
2
N)
for all but at most O(ε
1
2
N) values of u. Therefore
u∈Z
N
[E
∩ (E
+u)[[E ∩ (E + 2u)[[E ∩ (E + 3u)[
=
u∈Z
N
[E
∩ (E
+u)[(δ
2
N +O(ε
1
2
N))
2
+O(ε
1
2
N
4
)
=(δ
4
N
2
+O(ε
1
2
N
2
))
u∈Z
N
[E
∩ (E
+u)[ +O(ε
1
2
N
4
)
=(δ
4
N
2
+O(ε
1
2
N
2
))[E
[
2
+O(ε
1
2
N
4
)
=(δ
4
N
2
+O(ε
1
2
N
2
))δ
2
N
2
+O(ε
1
2
N
4
)
=δ
4
δ
2
N
4
+O(ε
1
2
N
4
).
That’s the end of the proof, all the left is to show (4) and (5).
014
3.1 The proof of (4)
Proposition 3.5. We have
s∈Z
N
[
j∈E∩(P
0
+s)
exp(2πiφ
s
(j)/N)[ = O(εN[P
0
[) (12)
for any Z
N
arithmetic progression P
0
of length M
C
and any non
constant quadratic functions φ
0
, φ
1
, , φ
N−1
with integer coeﬃcients.
Assume this proposition, we show that (4) is the corollary of it.
Corollary 3.6. 1
E

˙
A
∞
= O(εN).
Proof : Assume Proposition 3.5, we have
[
s∈Z
N
j∈E∩(P
0
+s)
exp(2πiφ
s
(j)/N)[ = O(εN[P
0
[).
015
For a ﬁxed 1 n N −1, take φ
s
(j) = nj, we get:
O(εN[P
0
[) = [
s∈Z
N
j∈E∩(P
0
+s)
exp(2πinj/N)[
= [
s∈Z
N
j∈P
0
+s
1
E
(j) exp(2πinj/N)[
= [[P
0
[
j∈Z
N
1
E
(j) exp(2πinj/N)[
= [[P
0
[
ˆ
1
E
(n)[,
and therefore we get (4) since n is nonzero. The lemma is done.
We shall prove Proposition 3.5. Fix the functions φ
0
, φ
1
, , φ
N−1
and the Z
N
arithmetic progression P
0
, we can reduce to the case when
P
0
is the arithmetic progression [0, r) for some M
C
< r < N since N is
prime.
Deﬁnition 3.7. We say Z
N
arithmetic progressions P
1
, P
2
, , P
n
evenly
cover Z
N
if the function
n
j=1
1
P
j
is a constant on Z
N
.
016
Lemma 3.8. Let P
1
, P
2
, , P
n
be Z
N
arithmetic progression of length
M
3
which evenly cover Z
N
. Then we have
n
j=1
[[E ∩ P
j
[ −δ[P
j
[[ = O(ε
n
j=1
[P
j
[). (13)
Proof. From (3), we have
[E ∩ P
j
[ −δ[P
j
[ = O(ε[P
j
[),
if [E ∩ P
j
[ −δ[P
j
[ 0. Write f =
n
j=1
1
P
j
, then
n
j=1
([E ∩ P
j
[ −δ[P
j
[) =
x∈E
f −δ
n
j=1
[P
j
[ =
[E[
N
N
k=1
f −
[E[
N
n
j=1
[P
j
[ = 0
with the identity
n
j=1
[P
j
[ =
n
j=1
N
k=1
1
P
j
(k) =
N
k=1
n
j=1
1
P
j
(k) =
N
k=1
f.
017
Hence,
n
j=1
[[E ∩ P
j
[ −δ[P
j
[[ = 2
n
j=1
([E ∩ P
j
[ −δ[P
i
[)
+
= O(ε
n
j=1
[P
i
[).
Lemma 3.9. For every s ∈ Z
N
, we can partition P
0
+s = [0, r) +s into
arithmetic progressions P
s,1
, , P
s,n
s
of length [P
s,j
[ M
3
such that
for each 1 j n
s
, the function exp(2πiφ
s
()/N) is within o(1) of a
constant on P
s,j
, j = 1, , n
s
.
Assume this lemma for the moment and complete the proof of (12).
Proof of (12): Firstly we observe that when s ranges over Z
N
and
j ranges from 1 to n
s
, the progressions P
s,j
evenly cover Z
N
. By Lemma
3.8, we have
s∈Z
N
n
s
j=1
[[E ∩ P
s,j
[ −δ[P
s,j
[[ = O(ε
s∈Z
N
[P
s,j
[) = O(εN[P
0
[). (14)
018
By Lemma 3.9, we have
k∈E∩P
s,j
exp(2πiφ
s
(k)/N)
=
[E ∩ P
s,j
[
[P
s,j
[
k∈P
s,j
exp(2πiφ
s
(k)/N) +o([P
s,j
[)
=
[E ∩ P
s,j
[ −δ[P
s,j
[ +δ[P
s,j
[
[P
s,j
[
k∈P
s,j
exp(2πiφ
s
(k)/N) +o([P
s,j
[)
=δ
k∈P
s,j
exp(2πiφ
s
(k)/N) +O([[E ∩ P
s,j
[ −δ[P
s,j
[[) +o([P
s,j
[).
Summing this in j and taking absolute value, we get
019
[
k∈E∩(P
0
+s)
exp(2πiφ
s
(k)/N)[
=δ[
k∈P
0
+s
exp(2πiφ
s
(k)/N)[ +O(
n
s
j=1
[[E ∩ P
s,j
[ −δ[P
s,j
[[) +o([P
0
[).
Summing the above equation in s and using (14) we have
s∈Z
N
[
k∈E∩(P
0
+s)
exp(2πiφ
s
(k)/N)[
=δ
s∈Z
N
[
k∈P
0
+s
exp(2πiφ
s
(k)/N)[ +O(
s∈Z
N
n
s
j=1
[[E ∩ P
s,j
[ −δ[P
s,j
[[) +o(N[P
0
[)
=δ
s∈Z
N
[
k∈P
0
+s
exp(2πiφ
s
(k)/N)[ +O(εN[P
0
[)
From standard exponential sum estimates and the nonconstancy of φ
s
020
we observe that
k∈P
0
+s
exp(2πiφ
s
(k)/N) = o([P
0
[). (15)
and (12) follows from that.
It remains to prove Lemma 3.9. Fix s, without loss of generality we
can assume that s = 0. It suﬃces to partition [0, r) into Z
N
arithmetic
progression P
0,j
of length ∼ r
c
for some small c such that
[[
φ
0
(k
) −φ
0
(k)
N
[[ = o(1)
for all k, k
∈ P
0,j
. Let d
j
be the step size and k
j
the initial element of
P
0,j
. Assume φ
0
(k) = A
2
k
2
+A
1
k +A
0
, then
φ
0
(k
j
+ad
j
) −φ
0
(k
j
+bd
j
) = (a
2
−b
2
)A
2
d
2
j
+ (a −b)d
j
(2A
2
k
j
+A
1
).
It suﬃces to ﬁnd d
j
such that
[[
a
2
A
2
d
2
j
N
[[ = o(1),
021
[[
(2A
2
k
j
+A
1
)d
j
a
N
[[ = o(1)
hold for all [a[ r
c
. It thus suﬃces to obtain the conditions
[[
A
2
d
2
j
N
[[, [[
(2A
2
k
j
+A
1
)d
j
N
[[ = O(r
−3c
). (16)
By a quantitative version of Weyl’s theorem (Weyl: Let k 2,
t 2
2
32k
2
, N t and a ∈ Z
N
. Then there exists p t such that
[p
k
a/N[ t
−1/k2
k+1
. Here we take k = 2, t = r
c
7
.)
We can ﬁnd d r
c
7
such that
[[
A
2
d
2
N
[[ = o(r
−100c
).
Fix this d and partition [0, r) into arithmetic progressions P
1
, P
2
of step d and length ∼ r
5c
. For each such progression P
t
, let k
t
be an
element of it. By pigeonhole principle we can ﬁnd an integer m
t
= O(r
3c
)
such that
[[
(2A
2
k
t
+A
1
)m
t
d
N
[[ = O(r
−3c
).
022
Now partition each P
t
into arithmetic progressions P
0,j
of step m
t
d and
length ∼ r
5c
/m
t
M
3
. The ﬁrst condition of (16) is clear. To verify
the latter we observe that
k
j
= k
t
+ud
for some integer u = O(r
5c
), and thus
[[
(2A
2
k
j
+A
1
)m
t
d
N
[[ = [[
(2A
2
k
t
+A
1
)m
t
d
N
+
2A
2
um
t
d
2
N
[[
[[
(2A
2
k
t
+A
1
)m
t
d
N
[[ +[[
2A
2
um
t
d
2
N
[[
= O(r
−3c
) +O([[
A
2
d
2
N
[[r
5c
r
3c
)
= O(r
−3c
)
as desired.
023
3.2 The proof of (5)
Lemma 3.10. For any Z
N
arithmetic progression P of length M
C
<
[P[ = o(N) and (λ, µ) ∈ Z
N
Z
N
−¦(0, 0)¦ we have
k∈P
[
ˆ
1
E∩(E+k)
(λk +µ)[
2
= O(εN
2
[P[). (17)
Assume this lemma, we can now prove (5). Suppose for contradiction
that (5) failed, we get ∀c > 0, ∀N
0
> 0, ∃N > N
0
such that
k∈Z
N
1
E∩(E+k)

˙
A
∞
2cεN
2
.
For an arbitrary ﬁxed c and N. We can ﬁnd a set B ⊂ Z
N
of size
[B[ cεN such that
[[1
E∩(E+k)
[[
˙
A
∞
cεN.
In fact, let B be the set of all such k that
[[1
E∩(E+k)
[[
˙
A
∞
cεN.
024
Hence we have
2cεN
2
k∈Z
N
1
E∩(E+k)

˙
A
∞
=
1
E∩(E+k)

˙
A
∞
<cεN
1
E∩(E+k)

˙
A
∞
+
1
E∩(E+k)

˙
A
∞
cεN
1
E∩(E+k)

˙
A
∞
k∈Z
N
cεN +N
1
E∩(E+k)

˙
A
∞
cεN
1
= cεN
2
+N[B[.
Therefore [B[ cεN.
We can therefore ﬁnd a function φ : B → Z
N
−¦0¦ such that
[
ˆ
1
E∩(E+k)
(φ(k))[ cεN (18)
for all k ∈ B. Fix B, φ, and let Ω denote the graph of φ:
Ω := ¦(k, φ(k)) : k ∈ B¦.
Ω has considerable arithmetic structure:
025
Lemma 3.11. We have
¦(a, b, c, d) ∈ Ω
4
: a +b = c +d¦ (cε)
12
N
3
Proof. Square (18) and use the identity
[
ˆ
1
A
(n)[
2
=
u∈Z
N
s∈A∩(A+u)
exp(2πiun/N) (19)
for all A ⊂ Z
N
and n ∈ Z
N
, we have
u∈Z
N
s∈E∩(E+k)∩(E+u)∩(E+k+u)
exp(2πiuφ(k)/N) c
2
ε
2
N
2
.
Summing this over k ∈ B,
c
3
ε
3
N
3
k∈B
u∈Z
N
s∈E∩(E+k)∩(E+u)∩(E+k+u)
exp(2πiuφ(k)/N)
=
u∈Z
N
k∈Z
N
s∈E∩(E+k)∩(E+u)∩(E+k+u)
1
B
(k) exp(2πiuφ(k)/N)
=
u∈Z
N
k∈Z
N
s∈Z
N
1
E∩(E+u)
(s)1
E∩(E+u)
(s −k)1
B
(k) exp(2πiuφ(k)/N)
026
By Lemma 3.2, we have
c
3
ε
3
N
3
k∈B
u∈Z
N
s∈E∩(E+k)∩(E+u)∩(E+k+u)
exp(2πiuφ(k)/N)
u∈Z
N
[[1
E∩(E+u)
[[
2
[[1
E∩(E+u)
[[
2
[[1
B
() exp(2πiuφ()/N)[[
A
∞
N
u∈Z
N
[[1
B
() exp(2πiuφ()/N)[[
A
∞.
Hence,
u∈Z
N
[[1
B
() exp(2πiuφ()/N)[[
A
∞ c
3
ε
3
N
2
.
027
Since
u∈Z
N
[[1
B
() exp(2πiuφ()/N)[[
A
∞ c
3
ε
3
N
2
=
u∈Z
N
max
m∈Z
N
[
s∈Z
N
[[1
B
(s) exp(2πiuφ(s)/N) exp(2πims/N)[
=
u∈Z
N
max
m∈Z
N
[
(s,t)∈Z
N
×Z
N
1
Ω
(s, t) exp(2πi(ut +ms)/N)[
=
u∈Z
N
max
m∈Z
N
[
ˆ
1
Ω
(m, u)[,
we have
u∈Z
N
sup
m∈Z
N
[
ˆ
1
Ω
(m, u)[ c
3
ε
3
N
2
.
From H¨older, we thus have
u∈Z
N
sup
m∈Z
N
[
ˆ
1
Ω
(m, u)[
4
(cε)
12
N
5
028
and hence
u,m∈Z
N
[
ˆ
1
Ω
(m, u)[
4
(cε)
12
N
5
which by Plancherel becomes
[[1
Ω
∗ 1
Ω
[[ (cε)
12
N
3
as desired.
With this lemma and use Balog Szemer´edi theorem which asserts
that we can ﬁnd a subset Ω
⊂ Ω with [Ω
[ > c
ε
N and
[Ω
+ Ω
[ C
ε
N.
Remark. BalogSzemer´edi theorem: Let A = ¦a
1
, a
2
, , a
n
¦ be a
ﬁnite set of integers and if ¦(a
i
, a
j
, a
k
, a
l
) ∈ A
4
[a
i
+a
j
= a
k
+a
l
¦ cN
3
,
then there are positive integers c
1
and c
2
and a subset A
⊂ A such that
[A
[ c
1
N and [A
+A
[ c
2
N.
Apply Freiman’s theorem to conclude that Ω
is contained in a proper
multidimensional Z
N
Z
N
arithmetic progression P
1
+P
2
+ +P
d
= Q
029
of dimension d
ε
< 1 and cardinality at most C
ε
N. Assume [P
1
[ [P
i
[
for all 1 i d.
Claim that there exists a ∈ Z
N
Z
N
such that
[(a +P
1
) ∩ Ω[ c
ε
C
−1
ε
[P
1
[,
or else, we have
[Ω ∩ Q[
a∈P
2
+···+P
d
[(a +P
1
) ∩ Q[
a∈P
2
+···+P
d
c
ε
C
−1
ε
[P
1
[
= c
ε
C
−1
ε
[P
1
[[P
2
[ [P
d
[
c
ε
C
−1
ε
C
ε
N
= c
ε
N.
However observe that Ω
⊂ Ω ∩ Q we get [Ω ∩ Q[ [Ω
[ > c
ε
N, which
is a contradiction. Fix such a a, since Ω is a graph, a +P
1
can not be a
030
vertical line segment, hence there exists a Z
N
arithmetic progression P
0
of length N
1
d
ε
, and
k∈P
0
[
ˆ
1
E∩(E+k)
(φ(k))[
2
=
k∈P
0
[
ˆ
1
E∩(E+k)
(λk +µ)[
2
c
2
ε
2
N
2
[P
0
[
contradict to Lemma 3.10.
We have already shown (5) , all the remains is to prove lemma 3.10.
Proof of lemma 3.10: In the case λ = 0. From (19) and rewrite
the left hand side of (17) as
k∈P
u∈Z
N
s∈E∩(E+k)∩(E+u)∩(E+k+u)
exp(2πiu(λk +µ)/N).
Using the identity
u∈Z
N
f(u) =
1
[P[
u∈Z
N
l∈P
f(u +l),
031
[
u∈Z
N
l∈P
f(u +l) =
k∈Z
N
f(k)
u∈k−P
1 = [P[
k∈Z
N
f(k)]
we get
k∈P
[
ˆ
1
E∩(E+k)
(λk +µ)[
2
=
1
[P[
k∈P
u∈Z
N
l∈P
s∈E∩(E+k)∩(E+u+l)∩(E+k+u+l)
exp(2πi(u +l)(λk +µ)/N)
=
1
[P[
s∈E
u∈Z
N
k∈P
l∈P
1
E+k
(s)1
E+u+l
(s)1
E+k+u+l
(s) exp(2πi(u +l)(λk +µ)/N)
=
1
[P[
s∈E
u∈Z
N
k∈Z
N
l∈Z
N
1
(s−E)∩P
(k)1
(s−u−E)∩P
(l)1
(s−u−E)∩(P+P)
(k +l) exp(2πi(u +l)(λk +µ)/N)
1
[P[
s∈E,u∈Z
N
[
k∈Z
N
,l∈Z
N
f
1,s
(k)f
2,s−u
(l)f
3,s−u
(k +l)[
1
[P[
s∈E,u∈Z
N
[[f
1,s
[[
A
∞[[f
2,s−u
[[
2
[[f
3,s−u
[[
2
,
032
where
f
1,s
(k) = 1
(s−E)∩P
(k) exp(2πiφ
1
(k)/N),
f
2,s−u
(l) = 1
(s−u−E)∩P
(l) exp(2πiφ
2
(l)/N),
f
3,s−u
(k +l) = 1
(s−u−E)∩(P+P)
(k +l) exp(2πiφ
3
(k +l)/N),
φ
1
(k), φ
2
(l), φ
3
(k +l) are some nonaﬃne quadratic functions such that
φ
1
(k) +φ
2
(l) +φ
3
(k +l) = (u +l)(λk +µ).
Since
[[f
2,s−u
[[
2
2
= [
l∈P∩(s−u−E)
exp(4πiφ
2
(l)/N)[ [P[
and
[[f
3,s−u
[[
2
2
[P +P[ 2[P[
033
we get
k∈P
[
ˆ
1
E∩E+k
(λk +µ)[
2
1
[P[
s∈E
u∈Z
N
[P[[[f
1,s
[[
A
∞ = N
s∈E
[[f
1,s
[[
A
∞.
It suﬃces to show
s∈E
[[f
1,s
[[
A
∞ = O(εN[P[).
From proposition 3.5, we see
s∈E
[[f
1,s
[[
A
∞
=
s∈E
[
m∈Z
N
f
1,s
(m) exp(2πimn(s)/N)[
s∈Z
N
[
m∈(s−E)∩P
exp(2πi(φ
1
(m) +mn(s))/N)[
=
s∈Z
N
[
j∈(s−P)∩E
exp(2πi(φ
1
(s −j) + (s −j)n(s))/N)[
=O(εN[P[)
034
since φ
1
(s−)+(s−)n(s) is a nonconstant quadratic function for every
s.
In the case λ = 0 and µ = 0, By a rescaling, we may assume that
the progression P = [0, r). It then suﬃces to show that
m∈Z
N
ψ(
m
r
)[
ˆ
1
E∩(E+m)
(µ)[
2
= O(εN
2
r)
for some suitable real even bump function ψ. We can rewrite the left
hand side as
1
N
2
n,n
∈Z
N
r
ˆ
ψ(
r(n −n
)
N
)
ˆ
1
E
(n)
ˆ
1
E
(µ −n)
ˆ
1
E
(n
)
ˆ
1
E
(µ −n
)
where
ˆ
ψ is the Fourier transform of ψ on R. From (4) we have
ˆ
1
E
(n
)
ˆ
1
E
(µ −n
) = O(εN
2
)
and so it suﬃces to show that
n,n
∈Z
N
[
ˆ
ψ(
r(n −n
)
N
)[[
ˆ
1
E
(n)[[
ˆ
1
E
(µ −n)[ = O(N
2
)
035
But this follows from Schur’s test, Plancherel, and the rapid decay of
ˆ
ψ.
036
This action might not be possible to undo. Are you sure you want to continue?
We've moved you to where you read on your other device.
Get the full title to continue reading from where you left off, or restart the preview.